Studi Tentang Mental Imagery: Pengaruh Mental Imagery Terhadap Performa Olahraga dan Pemulihan Cedera Pada Atlet Menggunakan Analisis Bibliometrik - Pratama Putra, Adhitya Nugraha; Asi, Sali Rahadi (Institut Teknologi Bandung, 2025)
This study aims to examine the impact of mental imagery on sports performance and injury recovery in athletes through bibliometric analysis. The study utilizes data from the Scopus database to analyze the annual publication trends, most cited articles, prolific journals, frequently occurring keywords, and emerging research trends related to mental imagery. A total of 131 articles published between 1977 and 2024 were analyzed using VOSviewer, RStudio, and Scopus to visualize the data. The findings of this study indicate that mental imagery has a significant effect on enhancing athletic performance, both through the improvement of motor skills and injury recovery. The results provide new insights into research trends, gaps, and the future direction of mental imagery studies in sports, serving as a valuable reference for further research. Keywords: mental imagery, sports performance, injury recovery, athletes, bibliometric analysis.